Reevaluation of the acute toxicity of palytoxin in mice: Determination of lethal dose 50 (LD50) and No-observed-adverse-effect level (NOAEL). (15th April 2020) - Boente-Juncal, Andrea; Vale, Carmen; Camiña, Mercedes; Cifuentes, J. Manuel; Vieytes, Mercedes R.; Botana, Luis M.
Abstract: Palytoxin is an emergent toxin in Europe and one of the most toxic substances know to date. The toxin disrupts the physiological functioning of the Na + /K + -ATPase converting the enzyme in a permeant cation channel. Human intoxications by PLTX after consumption of contaminated fishery products are a serious health issue and can be fatal. Several reports have previously investigated the oral and intraperitoneal toxicity of PLTX in mice. However, in all cases short observation periods (24 and 48 h) after toxin administration were evaluated. In this work, single oral or intraperitoneal doses of PLTX were administered to healthy mice and surviving animals were followed up for 96 h. The data obtained here allowed us to calculate the oral and intraperitoneal lethal doses 50 (LD50 ) which were in the range of the values previously described. Surprisingly, the oral NOAEL for PLTX was more than 10 times lower than that previously described, a fact that indicates the need for the reevaluation of the levels of the toxin in edible fishery products. Highlights: Human intoxications by palytoxin are a serious health issue and can be fatal. In 2009 EFSA concluded that the toxicological database for palytoxin was limited. Single oral or intraperitoneal palytoxin was administered to mice and animals monitored for 96 h. The oral NOAEL was more than 10 times lower than that previously described. The intraperitoneal and oral LD50 did not increase with the longer observation times.